CORRELATION OF THE OPTICAL PROPERTIES AND INTERBAND TRANSITION OF VANADIUM THIN FILMS - Fouad, S.S. (Biological Sciences - PJSIR, 2022)
The possibilities of using the optical constants nand k of vanadium thin films, to calculate the free-electronoptical effective masses and relaxation time which were derived from the results, are discussed from the theoretical and experimental point of view. Throughout the optical constants, the optical conductivity <1 = <11 + <1z as well as the volume and surface energy loss function are derived. The interband contribution to the imaginary part of the dielectric constant is also obtained by subtracting the free electron contribution.